The snail and the whale - Donaldson, Julia; Scheffler, Axel (London : Macmillan Children's Books, 2003)
Wanting to sail beyond its rock, a tiny snail hitches a ride on a big humpback whale and then is able to help the whale when it gets stuck in the sand.
3.9
K-3.
K-3
Keywords: Snails -- Juvenile fiction; Whales -- Juvenile fiction; Snails -- Fiction; Stories in rhyme; Whales -- Fiction; Snails -- Fiction; Stories in rhyme; Whales -- Fiction; Picture books for children